2005
DOI: 10.4269/ajtmh.2005.72.688
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Malaria Screening and Targeted Treatment of United States–bound Montagnard Refugees From Cambodia in 2002

Abstract: In 2002, a group of Montagnard refugees living in Cambodia was accepted for resettlement in the United States. Pre-departure malaria screening and targeted treatment was conducted to prevent morbidity, and minimize the potential for local malaria transmission post-arrival. We screened 902 of 906 refugees using rapid diagnostic tests (RDTs), microscopy, and polymerase chain reaction (PCR) analysis. Twelve (1.3%) RDT results were positive and 28 (3.1%) were indeterminate. Microscopy confirmed Plasmodium species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Dramatic increases in sensitivity were observed with PCR, which detected two times as many infections as the OptiMAL Rapid Detection Tests (RDTs) and 25% more than microscopy. 5 Similar problems with sensitivity were reported in the study by Stauffer and others 31 using the Binax NOW ICT kit, whereas poor specificity and positive predictive values of RDTs in this population were described by Causer and others 32 using the OptiMAL kit. These issues with the performance of diagnostic tests within semi-immune, asymptomatic populations suggest that the prevalence of Plasmodium infections may have been underestimated in studies that used microscopy or RDTs for screening.…”
Section: Introductionmentioning
confidence: 75%
“…Dramatic increases in sensitivity were observed with PCR, which detected two times as many infections as the OptiMAL Rapid Detection Tests (RDTs) and 25% more than microscopy. 5 Similar problems with sensitivity were reported in the study by Stauffer and others 31 using the Binax NOW ICT kit, whereas poor specificity and positive predictive values of RDTs in this population were described by Causer and others 32 using the OptiMAL kit. These issues with the performance of diagnostic tests within semi-immune, asymptomatic populations suggest that the prevalence of Plasmodium infections may have been underestimated in studies that used microscopy or RDTs for screening.…”
Section: Introductionmentioning
confidence: 75%
“…The type of training that was provided to the dispensary level staff was, in all likelihood, more extensive than what could be provided during a national roll-out of RDTs. Although it has been suggested that novice technicians can competently use RDTs with minimal training[ 17 , 25 ], it was observed in this study that closer supervision, particularly during the first week, was needed in order to assure the health care workers that their techniques were appropriate. Comments continued up to the eighth week that more training and supervision was needed.…”
Section: Discussionmentioning
confidence: 88%
“…Currently, no refugee populations relocating to the United States from regions other than sub-Saharan African are from areas of hyper-or holoendemic malaria. Therefore, refugee populations relocating from other areas, except under special circumstances, 23,24 do not currently receive presumptive malaria treatment.…”
mentioning
confidence: 99%